SUBSTANTIATION ON SHORT TERM EFFICACY AND SAFETY OF INSULIN ANALOGUES IN NORTH INDIAN SUPERSPECIALITY HOSPITAL - Koladi, Mohammad Ali (INDONESIAN JOURNAL OF PHARMACY, 2014)
Diabetes mellitus is associated with high morbidity and mortality among patients and its prevalence is increasing at an alarming rate worldwide. Insulin analogues are reported to have better efficacy and safety as compared to conventional insulin therapy, however, substantiation of data in different geographical areas with genomic variation is yet to be established. The study was aimed to evaluate and compare the effectiveness and clinical safety profile of insulin analogues with regular insulin. In this prospective, randomized, observational study conducted at a Superspeciality hospital in India,78 diabetic patients on insulin therapy were recruited. The efficacy and safety markers of 24 patients on biphasic insulin analogue, 33 on recombinant insulin analogue and 21 on regular insulin were observed for 13 weeks. The collected data was statistically analyzed by using Instat software.The efficacy markers such as glycosylated hemoglobin, fasting and postprandial glucose values showed superior improvement with the insulin analogues at the end of 13 weeks study. Insulin analogues produced significantly fewer incidents of minor hypoglycemia without any significant alteration in BMI and weight gain. The results of our studies suggest that insulin analogues are safer and effective with regards to glycemic control and in the event of hypoglycemia over regular insulin.